Revitalizing the Role of Religion in Poverty Alleviation: A Critical Analysis of Gustavo Gutierrez’s Liberation Theology - Hakim, Lukman; Saleh, Fauzi; Mawardi, Mawardi; Azwarfajri, Azwarfajri (Prodi Studi Agama-Agama, 2025)
The widespread reality of poverty in Latin America prompted the emergence of liberation theology as a theological response to systemic injustice. Gustavo Gutierrez, one of the central figures in this movement, emphasized the strategic role of religion in dismantling oppressive structures and advocating for the liberation of the poor. This article aims to examine the role of religion in poverty alleviation through the lens of Gutierrez’s liberation theology. The study employs a qualitative approach using a descriptive-analytical method based on literature review. The findings reveal that Gutierrez distinguishes between two types of poverty: individual and structural. Individual poverty can be addressed through transformation of mindset, work ethic, and education. In contrast, structural poverty—which stems from systemic inequality and domination—requires radical social change grounded in principles of justice. Within this framework, religion is not merely a system of transcendental beliefs, but a liberative praxis capable of challenging injustice and advocating for the marginalized. This article affirms that liberation theology remains relevant not only as a matter of faith, but also as a critical framework for strengthening the role of religion in promoting social justice and siding with the oppressed.